Types of Erroneous Sounds in Pronouncing Speech Segments of the English Consonant Phonemes (Evidence from Indonesian Native Speakers as EFL Learners) - Pakpahan, Marnangkok (Multiverse: Open Multidisciplinary Journal, 2023)
Pronunciation stands as a pivotal language component and achieving proficient English oral communication hinges on mastering accurate English pronunciation. This study aims to identify erroneous sounds produced by English as a Foreign Language (EFL) students in English Phonology classes. Sixteen participants were selected using total population sampling, and oral examinations served as the primary data collection instrument. Employing a descriptive-qualitative method, the analysis focused on empirical facts and phenomena observed among participants. Results indicate that all participants (100%) exhibited improper pronunciation of English consonant phonemes /q/, /ð/, /?/, /d?/, and /?/, and associated words. Additionally, a majority (87.50%) struggled with /?/ and /t?/, while over half (62.50%) faced challenges with /f/ and /v/, and a subset (25%) encountered difficulties with /z/. These findings underscore persistent inaccuracies in English consonant pronunciation among EFL students, emphasizing the need for targeted interventions.